Improving Drug Delivery on Candida Albicans Using Geraniol Nanoemulsion - Silva Pontes, Cristiano [UNESP]; Garcia de Carvalho, Gabriel [UNESP]; Rosa Perin Leite, Andressa [UNESP]; Chorilli, Marlus [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP] (MDPI, 2023)
Geraniol (GE) is a monoterpene alcohol with excellent antifungal activity. However, its low solubility and high volatility impair its use. Nanoemulsions (NE) are excellent delivery systems for poorly soluble and volatile drugs, achieving controlled release of the active ingredient. The aim of this study was to improve the delivery of geraniol (GE) incorporated in NE against Candida albicans in order to evaluate the antibiofilm effect and cytotoxicity. Nanoemulsion containing 10% oil phase (cholesterol) (w/w), 10% surfactant (mixture of soy phosphatidylcholine and Brij 58; 1:2) (w/w), and 80% aqueous phase (phosphate buffer) (w/w) was synthesized. Incorporation of GE was carried out by sonication and the final compounds were characterized by hydrodynamic diameter, polydispersity index (PDI), and zeta potential (ZP), in addition to evaluation of physicochemical stability after 6 months and 1 year. The GE-NE effect was evaluated on Candida albicans biofilms and cytotoxic effect was evaluated on immortalized normal oral cell line NOK-Si. The diameter of GE-NE was 232.3 ± 2.7 nm and PDI 0.155 with exhibited homogeneity and stability in solution. GE-NE showed antibiofilm activity at a concentration of 75 μg/mL with reduction of >6.0 log10, and no cytotoxicity against NOK-Si cells at concentrations below 150 μg/mL was observed. GE-NE proved to be a promising candidate for prevention and treatment of fungal diseases.
Keywords: antifungal; biofilm; C. albicans; citotoxity; geraniol; nanoemulsion